Association of the SPTLC3 rs364585 polymorphism and serum lipid profiles in two Chinese ethnic groups. Issue 1 (December 2017) - Zhang, Qing-Hui; Yin, Rui-Xing; Gao, Hui; Huang, Feng; Wu, Jin-Zhen; Pan, Shang-Ling; Lin, Wei-Xiong; Yang, De-Zhai
Abstract Background Little is known about the association of the single nucleotide polymorphism (SNP) of rs364585 near serine palmitoyl-transferase long-chain base subunit 3 gene (SPTLC3 ) and serum lipid profiles. The present study was detected the association of theSPTLC3 rs364585 SNP and several environmental factors with serum lipid profiles in the Han and Jing populations. Methods Genotyping of theSPTLC3 rs364585 SNP was performed in 824 unrelated individuals of Han and 783 participants of Jing by polymerase chain reaction and restriction fragment length polymorphism combined with gel electrophoresis, and then confirmed by direct sequencing. Results There was no significant difference in either genotypic or allelic frequencies between Han and Jing, or between males and females of the both ethnic groups. The levels of serum low-density lipoprotein cholesterol (LDL-C) and the ratio of apolipoprotein (Apo) A1 to ApoB in Han; and total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and LDL-C in Jing were different between the A allele carriers and the A allele non-carriers (P < 0.05-0.001). Subgroup analysis according to sex showed that the levels of LDL-C in Han males; TC and LDL-C in Jing males; and HDL-C and LDL-C in Jing females were different between the A allele carriers and the A allele non-carriers (P < 0.05-0.001), the A allele carriers had higher LDL-C and TC levels, and lower HDL-C levels than the A allele non-carriers. Serum lipid traits were also associated with several environmental factors in the Han and Jing populations, or in males and females of the both ethnic groups. Conclusions The present study demonstrates the association between theSPTLC3 rs364585 SNP and serum TC, HDL-C and LDL-C levels in our study populations. These associations might have ethnic- and/or sex-specificity. Trial registration Retrospectively registered.